Prime Minister Decree No. 1115/2012 On The Formation Of The Ministerial Group For The Settlement Of Investment Related Disputes As Amended By Decrees Nos. 714/2013 And 363-1092/2014 = قرار رئيس مجلس الوزراء رقم 1115 لسنة 2012 بشأن تشكيل المجموعة الوزارية لفض المنازعات الخاصة بالاستثمار معدل بالقرارات أرقام 714/2013 و 363-1092/2014 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic